2007
DOI: 10.4103/0971-6203.37478
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and audit of radiation dose during percutaneous transluminal coronary angioplasty

Abstract: The percutaneous transluminal coronary angioplasty (PTCA) is one of the interventional procedures which impart high radiation doses to patients compared to the other cardiologic procedures. This study intends to audit and optimize radiation dose imparted to patients undergoing PTCA. Forty-four patients who underwent PTCA involving single or multiple stent placement guided under cardiovascular X-ray machine were included in the study. Radiation doses were measured using dose area product (DAP) meter for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…24 As part of dose audits over the past decade, local, and regional DRLs were set up for radiological investigations in our tertiary referral center. ►Table 2 shows radiation dose audit of interventional procedures from our center in comparison with DRL values reported by Hart et al 17,18,[25][26][27][28][29][30][31][32][33][34] The values reported from our study are well within the reported DRLs, ensuring periodic dose monitoring and modification of work practices. Interventional procedures involve extensive use of tube angulations such left anterior oblique (LAO), right anterior oblique combined with cranial and caudal angles (CAU).…”
Section: Performing Radiation Dose Auditsupporting
confidence: 78%
See 1 more Smart Citation
“…24 As part of dose audits over the past decade, local, and regional DRLs were set up for radiological investigations in our tertiary referral center. ►Table 2 shows radiation dose audit of interventional procedures from our center in comparison with DRL values reported by Hart et al 17,18,[25][26][27][28][29][30][31][32][33][34] The values reported from our study are well within the reported DRLs, ensuring periodic dose monitoring and modification of work practices. Interventional procedures involve extensive use of tube angulations such left anterior oblique (LAO), right anterior oblique combined with cranial and caudal angles (CAU).…”
Section: Performing Radiation Dose Auditsupporting
confidence: 78%
“…The DAP is the most reliable measurement technique for dynamic examinations such as fluoroscopy in which the projection technique and the technique parameters are continually varying. [17][18][19] DAP (unit: Gycm 2 ) helps in the estimation of radiation doses from complex interventional examinations and provides a useful indication of overall patient dose rather than measurement of surface dose. 20,21 DAP is particularly useful for assessing and comparing radiation doses from complex interventions and in establishing diagnostic reference levels (DRLs) which serve as a reference for practicing interventionalists.…”
Section: Performing Radiation Dose Auditmentioning
confidence: 99%
“…A common dose reduction technique reported in the literature for both patients and operators is the avoidance of steep LAO with cranial-caudal angulations whenever possible, as large exposure factors are selected for oblique angulations [27,35]. Kuon and colleagues [25,26] reported a 2.5-fold increase in DAP with the typical cranial LAO 60˚/20˚angulation for visualisation of the bifurcation into LAD and diagonal compared with the cranial posterior-anterior (PA) 0˚/30˚.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found that the radiation dose varies significantly according to tube angulations, particularly in the combination of steep left anterior oblique (LAO) with cranial or caudal angulations [24][25][26][27]. However, there are no published data on whether the radiation dose with biplane or single-plane imaging during coronary angioplasty differs between the three vascular territories: right coronary artery (RCA), left anterior descending (LAD) and left circumflex/intermediate (LCX).…”
mentioning
confidence: 97%
“…Sandborg et al (11) published DAP values of 40 Gy•cm 2 for femoral procedures and 69 Gy•cm 2 for radial procedures. Livingstone et al (12) reported DAP values before and after optimisation by increasing the existing filtration and by increasing tube potentials.…”
Section: Discussionmentioning
confidence: 99%